Who's who in Philippine history - Kabahar, Pio A. 1892- (Tahanan Books, 1995)
This book was published to give the Filipino people a quick reference tool on Filipino who had made a significant contribution in the Philippine History. "Who's who in Philippine History covers major fields of endeavor including education, science, literature, politics, religion, theatre, dance, music, film, commerce, architecture, sports and medicine. Among its distinguished cast of characters are presidents, martyrs, religious leaders, revolutionary fighters and reformers, peace-makers, athletes, Muslims and a lot more." It also includes biographies of these people. It has more than 530 entries spanning four centuries. Includes an Index.